2017
DOI: 10.1002/mnfr.201700074
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl-γ-valerolactones, flavan-3-ol colonic metabolites, protect brown adipocytes from oxidative stress without affecting their differentiation or function

Abstract: Phenyl-γ-valerolactones and their sulphated forms do not influence brown adipocyte development or function at physiological or supraphysiological doses in vitro, but they are active protecting brown adipocytes from increased reactive oxygen species production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…The plasma C max of phenyl-γ-valerolactone derivatives are usually achieved at 4 to 6 h after consuming proanthocyanidin-rich foods, such as cranberry, tea and cocoa, and remain constant for several hours [ 8 , 25 , 26 ]. Bioactivity of phenyl-γ-valerolactones have been investigated both in vitro and in vivo, suggesting their role in regulation of inflammation, inhibition of cancer cell proliferation, reduction of systolic blood pressures, reduction of fat accumulation and prevention of urinary tract infections [ 7 , 27 , 28 , 29 , 30 ]. Thus, the significantly increased plasma and urinary concentration of phenyl-γ-valerolactones after a 4-week RRB and RRB+FOS intervention may result in associated health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma C max of phenyl-γ-valerolactone derivatives are usually achieved at 4 to 6 h after consuming proanthocyanidin-rich foods, such as cranberry, tea and cocoa, and remain constant for several hours [ 8 , 25 , 26 ]. Bioactivity of phenyl-γ-valerolactones have been investigated both in vitro and in vivo, suggesting their role in regulation of inflammation, inhibition of cancer cell proliferation, reduction of systolic blood pressures, reduction of fat accumulation and prevention of urinary tract infections [ 7 , 27 , 28 , 29 , 30 ]. Thus, the significantly increased plasma and urinary concentration of phenyl-γ-valerolactones after a 4-week RRB and RRB+FOS intervention may result in associated health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report on the metabolic fate of (+)-catechin in rabbits by Watanabe et al [9], there have been intensive pharmacokinetic studies on DHPV [10][11][12] after the intake of a single flavan-3-ol or polyphenol-rich foods in various living organisms for the past half century. However, investigation on its biological effects were relatively rare, except for a few reports [13][14][15][16]. Despite the lack of studies on DHPVs' role in the biological system, several papers recently reported that DHPV exhibits a protective effect against UV-induced skin inflammation [17] or photoaging [18].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in obesity, a major element in the development of MetS, in response to the consumption of foods rich in flavan-3-ols (e.g., green tea), has been attributed to the role of their content on polyphenolic metabolites in increasing energy expenditure via the modulation of cell differentiation and thermogenesis in adipose tissues [ 231 ]. However, when tested in vitro, the flavan-3-ol metabolites [5-(3’,4’-dihydroxyphenyl)-γ-valerolactone, 5-(3’-hydroxyphenyl)-γ-valerolactone-4’-O-sulfate, and 5-phenyl-γ-valerolactone-3’,4’-di-O-sulfate] did not stimulate cell differentiation and the activation of immortalized pre-adipocytes.…”
Section: Polyphenol Metabolitesmentioning
confidence: 99%
“…In addition, none of the metabolites regulated the expression of the uncouple protein 1, nor the main transcription factors implicated in brown adipocyte genesis. Nevertheless, both 5-(3’,4’-dihydroxyphenyl)-γ-valerolactone and 5-(3’-hydroxyphenyl)-γ-valerolactone-4’-O-sulfate protected immortalized pre-adipocytes from H 2 O 2 generated OxS [ 231 ]. In a recent clinical trial, Rodriguez-Mateos et al [ 288 ] showed that cranberry juice given to healthy volunteers improved, in a concentration- and time-dependent manner, the flow-mediated vasodilatation, an early clinical sign in the development of atherosclerosis.…”
Section: Polyphenol Metabolitesmentioning
confidence: 99%